Methods of Gold and Silver Nanoparticles Preparation - Slepička, Petr (Materials (Basel), 2019)
The versatile family of nanoparticles is considered to have a huge impact on the different fields of materials research, mostly nanoelectronics, catalytic chemistry and in study of cytocompatibility, targeted drug delivery and tissue engineering. Different approaches for nanoparticle preparation have been developed, not only based on “bottom up” and “top down” techniques, but also several procedures of effective nanoparticle modifications have been successfully used. This paper is focused on different techniques of nanoparticles’ preparation, with primary focus on metal nanoparticles. Dispergation methods such as laser ablation and vacuum sputtering are introduced. Condensation methods such as reduction with sodium citrate, the Brust–Schiffrin method and approaches based on ultraviolet light or biosynthesis of silver and gold are also discussed. Basic properties of colloidal solutions are described. Also a historical overview of nanoparticles are briefly introduced together with short introduction to specific properties of nanoparticles and their solutions.